The extended modified male Z-plasty necklift for correction of severe aging changes of the neck with secondary improvement of the lower third of the face - Gary J Nishioka (International Journal of Dermatology and Clinical Research - Peertechz Publications, 2018)
The male Z-plasty necklift (MZPN) is a well described procedure [1-4], specifi cally used for men with severe aging neck changes who cannot be achieve a satisfactory aesthetic outcome with other necklift procedures that are performed through a submental incision. Other direct excision male necklift techniques have also been described [5-9]. The MZPN is not felt suitable for women because of the visible anterior neck incision which does not camoufl age well with thinner smooth non-hair bearing neck skin, and an elective long visible scar located here is generally considered socially unacceptable. However, for men with severe aging changes of the neck this procedure produces results with a very high level of patient and surgeon satisfaction. Furthermore, surgical morbidity is very low with rapid recovery, and can easily be performed in the office surgery suite with local anesthesia with or without light sedation.